Предмет: Алгебра,
автор: Maksim3344
Выполните умножение: (a+3)(b-7)
(8+3x)(2y-1)
(3x(квадрат)-1)(2x+1)
(5c-1)(c(квадрат)-5c+1)
-8(y-1)(y+5)
Ответы
Автор ответа:
0
-8(y-1)(y+5)(a+3)(b-7)=ab-7a+3b-21
(8+3x)(2y-1)=16y-8+6xy-3x=-3x+6xy+16y-8
(3x²-1)(2x+1)=6x³+3x²-2x-1
(5c-1)(c²-5c+1)=5c³-25c²+5c-c²+5c-1=5c³-26c²+10c-1
-8(y-1)(y+5)=-8(y²+5y-y-5)=-8y²-32y+40
Похожие вопросы
Предмет: Биология,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: География,
автор: askarzhasulan813
Предмет: Физика,
автор: Аноним
Предмет: Информатика,
автор: Vorona99